A review of the razorfishes (Perciformes: Labridae) of the eastern Pacific Ocean - Victor, Benjamin C. (2001)
Several new species of the razorfish genus Xyrichtys have been discovered recently in the tropical eastern Pacific region. The taxonomy of this group of fishes is not clear, since juveniles, females, and males often have different color patterns and morphologies, and some species descriptions are incomplete. We review the members of this genus in this region based on our recent collections and describe the juvenile, initial, and terminal phase color patterns of the Cape razorfish, Xyrichtys mundiceps. We question the validity of Xyrichtys perlas, which appears to represent the initial phase of X. mundiceps. We conclude that six species of Xyrichtys are present in the tropical eastern Pacific, including one undescribed species we have collected from the Galapagos Islands and one uncollected new species from the Revillagigedos Islands. Xyrichtys mundiceps is found in Baja California and in Panama. Xyrichtys pavo is a large species found throughout the Indo-Pacific and eastern Pacific. Xyrichtys victori is a colorful species native to the Galapagos and Cocos Islands, and Xyrichtys wellingtoni is apparently endemic to Clipperton Atoll. The undescribed species is known only from the Galapagos Islands and has a dark-colored juvenile with extended first dorsal fin rays that are not separated from the remainder of the fin. The terminal phase of this species is unknown. We present keys to the known juvenile and initial phase stages of five species. In addition, we document the allometric growth of the head of razorfishes and show that the head shape of small individuals of Xyrichtys razorfishes is no different from that of the razorfish genus Novaculichthys, and therefore we suggest caution in using this character to distinguish these genera.